2022
DOI: 10.3390/jof9010052
|View full text |Cite
|
Sign up to set email alerts
|

Lignin and Its Pathway-Associated Phytoalexins Modulate Plant Defense against Fungi

Abstract: Fungi infections cause approximately 60–70% yield loss through diseases such as rice blast, powdery mildew, Fusarium rot, downy mildew, etc. Plants naturally respond to these infections by eliciting an array of protective metabolites to confer physical or chemical protection. Among plant metabolites, lignin, a phenolic compound, thickens the middle lamella and the secondary cell walls of plants to curtail fungi infection. The biosynthesis of monolignols (lignin monomers) is regulated by genes whose transcript … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 122 publications
0
32
0
Order By: Relevance
“…5-hydroxylase, cinnamoyl CoA reductase, CAD, and peroxidases/laccases. 24,[109][110][111][112][113][114][115][116][117][118] The functions of the individual proteins in regulating lignin biosynthesis and genetic manipulations that influence lignin biosynthesis can be accessed from our previous review of article (Figures 1 and 2). 24 DNA motifs are rich in adenosine and cytosine (AC) elements that promote and largely influence lignin biosynthesis.…”
Section: Regulation Of Lignin Biosynthesismentioning
confidence: 99%
See 3 more Smart Citations
“…5-hydroxylase, cinnamoyl CoA reductase, CAD, and peroxidases/laccases. 24,[109][110][111][112][113][114][115][116][117][118] The functions of the individual proteins in regulating lignin biosynthesis and genetic manipulations that influence lignin biosynthesis can be accessed from our previous review of article (Figures 1 and 2). 24 DNA motifs are rich in adenosine and cytosine (AC) elements that promote and largely influence lignin biosynthesis.…”
Section: Regulation Of Lignin Biosynthesismentioning
confidence: 99%
“…24,[109][110][111][112][113][114][115][116][117][118] The functions of the individual proteins in regulating lignin biosynthesis and genetic manipulations that influence lignin biosynthesis can be accessed from our previous review of article (Figures 1 and 2). 24 DNA motifs are rich in adenosine and cytosine (AC) elements that promote and largely influence lignin biosynthesis. The transcriptional factor MYB is rich in AC elements and mediates lignin synthesis gene expression; for example, MYB46 and its homologue MYB83 regulate the expression of lignin synthetic genes.…”
Section: Regulation Of Lignin Biosynthesismentioning
confidence: 99%
See 2 more Smart Citations
“…This is because lignin is a natural antimicrobial polymer. Plants deposit lignin in the secondary cell wall to defense against pathogens . Research with isolated lignin indicated that the antimicrobial mode of action of lignin involves the affinity to microbial cell surface and causing membrane destabilization, which do not induce drug resistance in pathogenic microbes .…”
Section: Introductionmentioning
confidence: 99%